MYSIR’s Abstracts 3: Annual Scientific Meeting 2022 - Interventional Radiology, Malaysian Society of (The Interventionalist Journal, 2022)
MYSIR’s Abstracts 3 1. EP07: CASE OF REFRACTORY AND RECURRENT RADIAL ANEURYSMAL BONE CYST TREATED WITH TRANS-ARTERIAL EMBOLISATION AND PERCUTANEOUS SCLEROTHERAPY – OUR EXPERIENCE 2. EP08: ANGIOEMBOLISATION OF CREMASTERIC ARTERY FOR SCROTAL HAEMATOMA FOLLOWING HERNIAL REPAIR 3. EP09: EMBOLIZATION OF A HIGHLY VASCULAR CERVICAL SPINE TUMOUR AND IMAGING ASSESMENT PRIOR TO SURGERY 4. EP10: PRE-OPERATIVE EMBOLIZATION OF ANGIOSARCOMA OF THE HEAD: A CASE REPORT 5. EP11: PSEUDOMYXOMA PERITONEI MIMICKING RUPTURED LIVER ARTERIOVENOUS MALFORMATION – AN UNCOMMON PRESENTATION OF A HIGH GRADE LIVER SARCOMA 6. EP12: RUPTURED CYSTIC ARTERY PSEUDOANEURYSM AS A COMPLICATION OF ACUTE CALCULOUS CHOLECYSTITIS – A CASE REPORT